Engineering Peace and Justice The Responsibility of Engineers to Society - Vesilind, P. Aarne (Springer London : Imprint: Springer, 2010)
The engineering profession has evolved considerably from the early engineers who were, almost without exception, employed in the making of war or in the defense of nations. Civil engineering emerged in the 18th century, providing an alternative for many engineers, and today there is a strong movement in the development of "peace engineering" - the pro-active use of engineering skills in the promotion of peace. Engineering Peace and Justice: The Responsibility of Engineers to Society details the history of the profession, including its ethical commitment to the public good, and shows how engineers have, in the past, served their clients as either military or civilian engineers. As well as presenting a discussion of the evolution of engineering, the book also examines concepts of ethical engineering, including the engineer's duty to society; engineering's relationship to war and peace; and the engineer's commitment to the environment. The final section details some stories of contemporary engineers who have used their technical skills in the promotion of peace, becoming "peace engineers". Engineering Peace and Justice: The Responsibility of Engineers to Society will be of interest to anyone involved in the engineering profession. Students contemplating careers in engineering will also find this book an inspiring guide to more vocational roles in the field.